Juxta-adrenal Ancient Schwannoma: A Rare Retroperitoneal Tumor - Wollin, Daniel A (Rev Urol, 2015)
Retroperitoneal schwannoma is a rare tumor that is often misdiagnosed as malignancy due to a concerning appearance on cross-sectional imaging. Pathology and immunohistochemistry form the gold standard for diagnosis; as such, local excision is the treatment of choice for this disease. We present two cases of juxta-adrenal ancient schwannoma that were treated with adrenalectomy and discuss the current literature regarding this entity.